The Role of Political Connections and Management Risk Appetite on Financial Distress in the Indonesian Banking Sector - Moh. Ridwan Pamungkas; Intan Kurnia Permatasari (Manunggal Halim Jaya, 2027)
In heavily regulated banking sectors, understanding how managerial risk preferences and political linkages influence systemic financial stability is paramount. This study examines the effects of management risk appetite and political connections on financial distress, and tests political connections as a moderating variable among publicly listed banks in Indonesia during 2019–2024, controlling for bank age, board size, institutional ownership, and net interest margin. Using purposive sampling, 42 banks were selected, yielding 252 firm-year observations analyzed via panel data regression using a Random Effects Model. The results reveal that management risk appetite has no significant direct effect on financial distress, suggesting that strict regulatory oversight tempers internal risk preferences. In contrast, political connections significantly exacerbate financial distress, undermining overall bank health. Political connections do not significantly moderate the impact of management risk appetite on financial distress. Among the control variables, net interest margin significantly improves financial stability. This study contributes to the corporate governance literature by providing empirical evidence from an emerging market on the destabilizing role of political ties in banking distress. The findings offer practical insights for regulators and bank boards to strengthen oversight on political connections. However, the model exhibits limited explanatory power. Future research should incorporate broader governance mechanisms and specific political tie dimensions to extend these findings.